Adverse drug events, comorbidities, and older age are statistically more prevalent in COVID-19 hospitalized patients treated with remdesivir than tocilizumab in a private hospital from southern Brazil - Wolf, Jonas Michel; Gubert Borges, Bianca; Pereira Fagundes, Pamela; de Souza, Vinicius; Brenner, Aline; Petek, Helena; Michelon dos Santos, William; Gasparetto Maccari, Juçara; Rohsig, Vania; Parrini Mutlaq, Mohamed; Nasi, Luiz Antonio (Clinical and Biomedical Research, 2023)
Introduction: COVID-19 pandemic spread rapidly with more than 560 million cases and 6.3 million deaths. Since the emergence of the COVID-19 pandemic, the purpose of treating the disease has become a priority. To date, there is no consensus on the best pharmacological therapy. The objective of the present study was to compare two pharmacological therapies, evaluating the adverse drug events, one on the label (remdesivir) and another off-label (tocilizumab) used to treat patients hospitalized for COVID-19 in a private hospital in southern Brazil. Methods: The study analyzed data from hospital records of 124 patients hospitalized with COVID-19 (n=80 treated with tocilizumab and n=34 with remdesivir), confirmed by RT-PCR, between 2020 and 2021. Poisson regression models with prevalence ratio (PR) with 95% confidence intervals (95%CI) were applied to confirm the association between dependent variables and with treatment used. Results: Patients treated with remdesivir were older than those treated with tocilizumab (median 70.0 vs 61.0; p=0.02). Adverse drug effects were more frequent in patients treated with remdesivir (35.3%) than tocilizumab (3.8%) (p <0.01). Comorbidities ≥3 were 58.8% in the remdesivir group and 25.0% in the tocilizumab (p=0.01). In the multivariate analysis, patients treated with remdesivir had a higher prevalence of advanced age (PR:1.58; 95%CI:1.11–3.05), adverse reaction (PR:13.21; 95%CI:3.74–54.96), mechanical ventilation (PR: 5.60; 95%CI: 1.51-11.20), comorbidities ≥3 (PR:4.11; 95%CI:1.76–10.56), hypertension (PR:2.47; 95%CI:1.08–5.98), cardiac disease (PR:3.15; 95%CI:1.35–7.75), dyslipidemia (PR:3.83; 95%CI:1.15-13.55), cancer (PR:3.81; 95%CI:1.33-13.21) and kidney disease (PR:4.21; 95%CI:1.02–19.66). Conclusion: Rendesivir-treated patients had more adverse events, were older, and had more comorbidities than tocilizumab-treated patients.